Pengaruh Penggunaan Teknologi pada Monitoring Ketersediaan Beras di Dinas Ketahanan Pangan dan Pertanian Surabaya - Lailatul Badriah; Wahyu Santoso; Noor Rizkiyah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Monitoring is a process that involves collecting relevant data, proper analysis, and ensuring that a program is well so that can achieve its goals. The use of digital technology monitoring is important in this modern era. Human resource skills in utilizing technology are crucial for data entry activities, which impact data accuracy. However, in practice this often a challenge in the field. The purpose of this study is to analyze the impact of digital technology using digital technology with the Technology Acceptance Model approach to monitoring rice availability. This research is located at the Surabaya Food Security and Agriculture Service which is a government agency in overseeing and monitoring the activities of agriculture and food sector activities, one of which is monitoring the availability of rice in the city of Surabaya. This research method use qualitative descriptive and multiple linear regression analysis with primary data collection and a satured sample size of 30 respondents. The variables of this study are perceived ease of use (X1), perceived usefulness (X2), technology user behavior (X3), and digital-based rice availability monitoring (Y). The results showed that perceived ease of use and user behavior have a significant and positive influence on rice availability monitoring of 59,6% and 44,8%. However, perceived usefulness in negative value of 23,4% which means that the technology is considered valid but implementation not optimal. This requires increased monitoring through staff and surveyor training and developing system components based on user needs to encourage maximum use of technology.